Harmony and Reconciliation in Daoism and Christianity: Contributions to a Contemporary Identity Discourse - Tophoff, Michael (Asia journal of theology, 2022)
In this article, the contemporary identity discourse is highlighted within a Christian perspective of reconciliation, and a Daoist perspective of harmony. Reconciliation is placed in the context of the Hebrew Bible, focusing on the concepts of liberation, covenance, sin and atonement, and on the ministry of Jesus. Daoist harmony is discussed within a cosmic system of interconnectedness, non-disruption and non-interference. Contributions of Christianity and Daoism to reconciliation and harmony are critically evaluated as to their relevance for the contemporary identity discourse.